Sobre Fausta Gantús, Florencia Gutiérrez, Alicia Hernández Chávez y María del Carmen León, La Constitución de 1824. La consolidación de un pacto mínimo - Frasquet Miguel, Ivana (Historia Mexicana, 2010)
-